Malignant Phyllodes Tumor and Acute Megakaryoblastic Leukemia Sharing a Common Clonal Origin. (17th December 2013) - Fløisand, Yngvar; Beiske, Klaus; Tjønnfjord, Geir Erland; Heldal, Dag; Bjerkehagen, Bodil; Revheim, Mona-Elisabeth; Heim, Sverre; Bruland, Øyvind Sverre; Hall, Kirsten Sundby; Tierens, Anne; Delabie, Jan
Abstract : There is a well-known association in male patients between mediastinal germ cell tumors (GCT) and hematologic malignancies, with a propensity towards acute megakaryoblastic leukemia. These rare malignancies have been shown to share a common clonal origin, often deduced from the finding of isochromosome 12p, i(12p), in cells from both the solid tumor and the leukemia, and thus are now known to represent different manifestations of the same clonal process. We treated a young female patient with a malignant phyllodes tumor followed by an acute megakaryoblastic leukemia and found several of the same marker chromosomes by karyotype analysis of cells from both the tumor and the leukemia implying a common clonal origin of the two. To the best of our knowledge, this has not been demonstrated in phyllodes tumors before, but indicates that the same type of leukemization may occur of this tumor as has been described in mediastinal GCT.